Cell-free supernatant of Devosia sp. (strain SL43) mitigates the adverse effects of salt stress on soybean (Glycine max L.) seed vigor index - Monjezi, Nadia; Yaghoubian, Iraj; Smith, Donald L. (Frontiers in Plant Science, 2023)
Soil salinity is a major constraint for soybean production, imposing negative impacts on seedling growth and uniformity in seed germination and thus reducing the yield of soybean. Plant growth-promoting bacteria and their bioactive metabolite(s) can be an environmentally sound way of increasing soybean production, helping plant seeds to germinate well, and establishing uniform, vigorous seedling stands under stressful conditions, such as salt-stress. With this objective, two experiments were performed, aiming to test 4 different culture media (YEM, TYE, TSA, and LBA) for growing a novel Devosia sp. (SL43 strain). and then evaluating cell-free supernatants (CFSs) from the Devosia sp. on germination of soybean (Glycine max L.) seeds under salinity stress. Soybean seeds were subjected to three salinity levels (0, 100, and 125 mM NaCl) and 6 levels of Devosia sp. CFS dilution (0, 1:1, 1:100, 1:250, 1:500, 1:1000). Findings obtained in this study indicate that YEM medium is appropriate for the in vitro cultivation of the Devosia strain. Our results indicated that salt stress considerably reduced seed germination rate and total seed germination, and the higher the concentration of NaCl, the greater the inhibitory effect on germination. The highest level of salinity decreased final seed germination (15%), germination rate (43.6%), root length (55.2%), root weight (39.3%), and seed vigor (68%), and it also increased mean germination time by 71.9%. Using Devosia-CFS, however, improved soybean germination, and the greatest effect at a 1:1 dilution level. At 125 mM NaCl application of CFS at 1:1 dilution increased final germination (17.6%), germination rate (18.6%), root length (162.2%), root weight (239.4%), seed vigor index (318.7%), and also shortening mean germination time by 19.2%. Seed germination, germination rate, length and dry weight of roots and seed vigor index correlated significantly and positively; mean germination time was shorter and so was negatively significantly correlated with the seed vigor index of soybean. The results illustrate that CFS produced by the novel Devosia sp. (SL43 strain) can successfully alleviate salt stress effects on soybean seed germination and that manipulating the chemical composition of the growth medium can influence the effectiveness of these bioactive metabolites.